Fatty acid and sugar compositions, and nutritional value of five wild edible mushrooms from Northeast Portugal - Barros, Lillian (2008)
The chemical composition and nutritional value of five wild edible mushroom species (Agaricus arvensis, Lactarius deliciosus, Leucopaxillus giganteus, Sarcodon imbricatus, Tricholoma portentosum) commonly consumed in the Tra´s-os-Montes region of Northeast Portugal was determined. Chemical composition evaluation included moisture, total oil content, crude protein, ash, carbohydrates, and nutritional value determination. The macronutrient profile in general revealed that the wild mushrooms were rich sources of protein and carbohydrates, and had low amounts of fat. On the basis of the proximate analysis, it can be calculated that an edible portion of 100 g of these mushrooms provides, on average, 28 kcal (118 kJ). The analysis of fatty acid composition, performed by gas–liquid chromatography coupled to a flame ionization detector, allowed the quantification of fifteen fatty acids. Unsaturated fatty acids and, in particular, oleic and linoleic acids, were predominant. The composition in individual sugars was also determined by high performance liquid chromatography coupled to a refraction index detector, mannitol and trehalose being the most abundant sugars.